On the class of harmonic mappings which is related to the class of bounded boundary rotation - Aydoğan, Melike; Kahramaner, Yasemin; POLATOĞLU, YAŞAR (Elsevier Science Inc, 360 Park Ave South, New York, Ny 10010-1710 Usa, 2015)
The class of bounded radius of rotation is generalization of the convex functions. The concept of functions bounded boundary rotation originated from Loewner (1917). But he did not use the present terminology. It was Paatero (1931, 1933) who systematically developed their properties and made an exhaustive study of the class V-k. In the present paper we will investigate the class of harmonic mappings which is related to the class of bounded boundary rotation. Crown Copyright (C) 2014 Published by Elsevier Inc. All rights reserved.
Keywords: Functions with bounded boundary rotation; Distortion theorem; Growth theorem; Harmonic mapping